Respostas

A melhor resposta!
2014-05-26T19:37:10-03:00
 simplificar quando possivel... )

a) ( 2√3 + 3√6) . 2√3  fazer a distributiva

(2√3 + 3√6).2√3 =
2√3 x2√3 + 3√6 x2√3=
2.2.√3√3 + 3.2√6√3 =
  4.√3.3   +  6.√6.3 =
  4√9       +  6.√18       fatorar  9| 3             18| 2
   12        + 12 + √2                  3| 3               9| 3
                                                 1/                 3| 3
                                                                      1/    
 4√9 = 4√3.3= 4√3²  = 4.3 = 12      e   6√18 = 6√2.3.3 = 6√2.3² = 6.3√2 = 12√2

( 2√3 + 3√6) . 2√3 =  4√9 + 6√18 = 12 + 12√2



b) ( √5 - √2) ²
(√5 - √2)(√5 - √2)    fazer a distributiva
√5√5 -√5√2 - √2√5 + √2√2 =
√5.5 - √5.2 - √2.5 + √2.2. =
√25  - √10  -  √10 +   √4 =
√25      - 2√10  + √4 =         fatorar   25| 5        10| 2         4 | 2
√5.5    - 2√2.5  + √2.2 =                     5| 5          5| 5         2 | 2
 √5²    - 2√10    +  √2²  =                     1/             1/            1/
   5     - 2√10     + 2 =
   7 - 2√10

                                                                               

1 5 1